Specification problems with information content of earnings: revisions and rationality of expectations and self‐selection bias* - ABDEL‐KHALIK, A. RASHAD (Contemporary Accounting Research, 1990)
This paper examines three possible specification problems with the research on information content of earnings disclosure. The first deals with the extent to which contemporaneous prediction errors are good surrogates for revisions of future earnings expectations and, hence, distributions of cash flows. This problem is elucidated by evaluating analysts' revisions of future earnings expectations as “relevant omitted variables.” The results show that the quality of such surrogation is high in the first quarter but low in the second. The second problem concerns the degree to which analysts' earnings forecasts are good surrogates for the market's own earnings expectations. Unbiasedness and orthogonality are the two properties examined. Although analysts' forecasts satisfy the unbiasedness property, the necessary condition of orthogonality is not satisfied. Hence, analysts' earnings forecasts are not Muthian rational expectations (i.e., they are not good surrogates for market forecasts). Consequently, the explanatory power of known empirical results is likely to be understated. The third specification issue is the significance of the self‐selection bias resulting from endogenous partitioning of samples into, say, good‐ and bad‐news portfolios. The Heckman‐Lee method of correcting for this type of selection (truncation) bias is applied. The results show significant self‐selection bias in both quarters but more so in the first than in the second quarter. Although applying the correction for this sample did not alter the general inferences, it did alter the marginal contribution of each explanatory variable and the explanatory power of the models. The results indicate that the information news about quarterly earnings is not homogeneous across different quarters in a fiscal period. The possibility that a “quarter effect” exists needs further investigation. Résumé. L'auteur se penche sur trois problèmes de spécification possibles en ce qui a trait à la recherche sur le contenu informatif des bénéfices publiés. Le premier de ces problèmes porte sur la mesure dans laquelle les erreurs prévisionnelles actuelles sont des substituts efficaces aux ajustements des bénéfices éventuels prévus et, partant, aux distributions de flux monétaires. On élucide ce problème grâce à l'évaluation des ajustements des bénéfices éventuels prévus effectués par les analystes, à titre de « variables pertinentes omises ». Les résultats de l'étude montrent que la qualité de cette substitution est élevée pour le premier trimestre mais faible pour le second. Le deuxième problème a trait à la mesure dans laquelle les prévisions de bénéfices des analystes sont des substituts efficaces aux prévisions de bénéfices au marché. L'auteur se demande si les prévisions des analystes sont non biaisées et orthogonales. Bien qu'elles se révèlent en effet non biaisées, elles ne respectent pas le critère d'orthogonalité. Les prévisions de bénéfices des analystes ne sont donc pas des prévisions rationnelles de Muthian (c'est‐à‐dire qu'elles ne sont pas des substituts efficaces aux prévisions du marché). On peut donc penser que le pouvoir explicatif des résultats empiriques connus est sous‐estimé. Le troisième problème de spécification est celui de la signification de la distorsion d'autosélection résultant du découpage endogène des échantillons, par exemple sous forme de portefeuilles dont les comptes rendus sont favorables ou défavorables. L'auteur applique la méthode de correction Heckman‐Lee prévue pour ce genre de distorsion de sélection (tronquée). Les résultats révèlent une importante distorsion d'autosélection pour les deux trimestres, plus marquée toutefois dans le premier que dans le second. Bien que l'application de la méthode de correction à cet échantillon n'ait pas modifié les inférences générales, elle a modifié la valeur explicative marginale de chaque variable et le pouvoir explicatif des modèles. Les résultats obtenus indiquent que l'information relative aux bénéfices trimestriels n'est pas homogène dans les différents trimestres d'un exercise financier. L'existence possible d'un « effet trimestre » doit faire l'objet de recherches plus approfondies.